Two Neonates with Congenital Hydrocolpos - Vydehi Murthy; Jessica Costalez; Julie Weiner; Kristin Voos (Case Reports in Pediatrics)
Introduction. Neonatal hydrocolpos is a rare condition. Hydrocolpos is cystic dilatation of the vagina with fluid accumulation due to a combination of stimulation of secretary glands of the reproductive tract and vaginal obstruction. The differential for a neonatal presentation of lower abdominal mass includes urogenital anomalies, Hirschsprung’s, disease or sacrococcygeal teratoma. Prenatal diagnosis and early newborn imaging studies leads to early detection and treatment of these cases. Case. We report here two cases of neonatal hydrocolpos with prenatal diagnosis of lower abdominal mass. Postnatally, ultrasound, MRI imaging, and cystoscopy confirmed large cystic mass as hydrocolpos with distal vaginal obstruction. Both patients had enlarged renal system secondary to mass effect. Conclusion. High index of suspicion for hydrocolpos in a newborn presenting with fetal diagnosis of infraumbilical abdominal mass will facilitate timely intervention and prevention of complications.